Kompleks Perairan Campurdarat: Dari Wisata Rawa Hingga Objek Perikanan, 1931-1941 - Fernando, Vigi Ilham; Rohmah, Nurul Baiti (Perkumpulan Program Studi Sejarah Se-Indonesia, 2025)
Rawa Campurdarat was initially used as a fishing site before transforming into a tourist destination under the Dutch East Indies community. Tourism activities, however, had to be suspended during the west monsoon due to rising water discharge that caused flooding in the Campurdarat District. Rawa Campurdarat also functioned as a fishery, with catches distributed beyond the region, significantly impacting the surrounding communities. This study aims to analyze the toponymy and conditions of the Rawa Campurdarat complex during the period 1931–1941, its transformation into both a tourist destination and a drainage system, and its role as a fishery within socio-economic and environmental contexts. The research employs historical methodology, consisting of four stages: heuristics, source criticism, interpretation, and historiography. The findings reveal that Rawa Campurdarat underwent significant transformations between 1931 and 1941, encompassing its function as a site, drainage system, and fishery activities. These transformations not only benefited the Colonial Dutch East Indies government but also had positive impacts on the local population, directly felt through the development of tourism and the local economy.